A new variety of Ipomoea triloba (Convolvulaceae) from Deccan plateau, India (Bangladesh Journal of Plant Taxonomy, 2023)
Ipomoea triloba L. var. deccansis D. K. Londhe & A.S.Bhukatar,var. nov.are described here as a new variety of Ipomoea triloba L. (Convolvulaceae) from the Western Ghat of the Deccan plateau, North Maharashtra, India. Observations in the field as well as in cultivation for three years showed that the variety retains its diagnostic characteristics and no intermediate exists. Detailed descriptions and photo plates are provided to facilitate the identification of this new variety.Bangladesh J. Plant Taxon. 30(1): 31-35, 2023 (June)